Adoption and perceived effectiveness of traditional practices to mitigate human-wild pig conflict situations - K. Senthilkumar; P. Mathialagan; C. Manivannan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Human–wild pig conflict is one of the main threats to farmers as wild pig destroys the growing crops completely. Krishnagiri district of Tamil Nadu was purposefully selected for the study as it ranked first in human-wild pig conflict incidents in Tamil Nadu. Farmers who had at least one wildlife conflict incidence in their lifetime were selected for this study during 2015- 16 on adoption and effectiveness of traditional practices to manage human-wild pig conflict situations. Sixty participants were selected using the snow ball sampling and data were collected using semi-structured interviews, complemented by free listing techniques, nonspecific prompting and reading back. A total number of nine traditional practices were identified and found that they were adopted at various levels. Further, boundary clearing, using metal cow bells and using shining tapes (100 %) were found to be most effective traditional method followed by fireworks/ crackers (75 %), noise making (72.2 %) and scarecrows (69.6 %). Although encouraging, these results require more widespread testing and demonstration to ensure their effectiveness at broader scales.